A Single Phase Inverter Using The Unipolar Sinusoidal Pulse Width Modulation Method - Iskandar, Muhammad Iskandar; Panca Mudjirahardjo; Bambang Siswojo (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2025)
The output power quality of conventional inverters often contains high levels of harmonic distortion, which can negatively affect the performance of connected electrical equipment. Therefore, a switching method capable of producing a near-ideal sinusoidal waveform with low total harmonic distortion (THD) is needed. This study presents the design and implementation of a single-phase inverter employing the Unipolar Sinusoidal Pulse Width Modulation (SPWM) technique to generate an output voltage waveform that closely resembles an ideal sine wave. Electrical energy produced by renewable energy requires a control system and an inverter. This inverter can convert direct current (DC) from renewable energy sources into alternating current (AC) with a wave quality that is close to a pure sinusoidal wave. The sinusoidal waves produced by this inverter are very important for maintaining optimal performance of sensitive electronic devices and reducing harmonic distortion which can damage electrical equipment. In this research, the design and manufacture of a single-phase H-Bridge inverter was carried out using the Unipolar Sinusoidal Pulse Width Modulation (USPWM) method. This method was chosenbecause it is capable of producing waveforms that are close to pure sinusoidal with lower Total Harmonic Distortion (THD) compared to conventional switching methods. This design includes a simulation stage using Matlab R2024b to analyzethe waveform and inverter performance before hardware implementation. The test results show that the inverter is ableto work well with a THD of 1.14%, an output power of 1,370Watt with a frequency of 50 Hz. These results show thatthe Unipolar SPWM method is very effective for controlling single-phase inverters for low to medium power applications.